Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium